Gut metabolite trimethylamine N-oxide induces aging-associated phenotype of midbrain organoids for the induced pluripotent stem cell-based modeling of late-onset disease - Lee, Youngsun; Kang, Ji Su; Ham, On-Ju; Son, Mi-Young; Lee, Mi-Ok (Frontiers in Aging Neuroscience, 2022)
Brain organoids are valuable research models for human development and disease since they mimic the various cell compositions and structures of the human brain; however, they have challenges in presenting aging phenotypes for degenerative diseases. This study analyzed the association between aging and the gut metabolite trimethylamine N-oxide (TMAO), which is highly found in the midbrain of elderly and Parkinson's disease (PD) patients. TMAO treatment in midbrain organoid induced aging-associated molecular changes, including increased senescence marker expression (P21, P16), p53 accumulation, and epigenetic alterations. In addition, TMAO-treated midbrain organoids have shown parts of neurodegeneration phenotypes, including impaired brain-derived neurotrophic factor signaling, loss of dopaminergic neurons, astrocyte activation, and neuromelanin accumulation. Moreover, we found TMAO treatment-induced pathophysiological phosphorylation of α-synuclein protein at Ser-129 residues and Tau protein at Ser202/Thr205. These results suggest a role of TMAO in the aging and pathogenesis of the midbrain and provide insight into how intestinal dysfunction increases the risk of PD. Furthermore, this system can be utilized as a novel aging model for induced pluripotent stem cell-based modeling of late-onset diseases.